2023
DOI: 10.3390/cancers15030656
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of p16 IHC in Classifying HPV-Driven OPSCC in Different Populations

Abstract: High-risk human papillomavirus (HPV) infection is a defined etiopathogenetic factor in oropharyngeal carcinogenesis with a clear prognostic value. The P16 IHC (immunohistochemistry) is a widely accepted marker for HPV-driven carcinogenesis in oropharyngeal squamous cell carcinoma (OPSCC); in the present paper, we discuss its reliability as a standalone marker in different populations. The literature suggests that rates of p16 IHC false positive results are inversely correlated with the prevalence of HPV-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In addition to the p16 + /HPV + cases we could identify in total 62 patients with p16 overexpression but HPV-DNA negative OPSCC (which is a rate of 4.9% of false positive p16 cases).This rate is comparable with the predicted rate of false positive p16 cases (3.8%) calculated by a recently published formula of Gallus et al [ 42 ]. Recent studies [ 9 , 37 , 40 42 ] found that patients with p16 + /HPV- OPSCC seem to have the same prognosis or only slightly better than p16-/HPV- cases. Consistent with these findings patients in our cohort with p16 + /HPV- OPSCC (and p16-/HPV + OPSCC) had a significant worse OS than patients with p16 + /HPV + OPSCC (additional Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition to the p16 + /HPV + cases we could identify in total 62 patients with p16 overexpression but HPV-DNA negative OPSCC (which is a rate of 4.9% of false positive p16 cases).This rate is comparable with the predicted rate of false positive p16 cases (3.8%) calculated by a recently published formula of Gallus et al [ 42 ]. Recent studies [ 9 , 37 , 40 42 ] found that patients with p16 + /HPV- OPSCC seem to have the same prognosis or only slightly better than p16-/HPV- cases. Consistent with these findings patients in our cohort with p16 + /HPV- OPSCC (and p16-/HPV + OPSCC) had a significant worse OS than patients with p16 + /HPV + OPSCC (additional Fig.…”
Section: Discussionsupporting
confidence: 74%
“…This is important to emphasize, as the definition of HPV positive OPSCC (whether it is defined only by overexpression of p16, independent of HPV-DNA or a combination of HPV-DNA and p16 positivity) is still discussed controversially in literature and not uniform [ 9 , 37 , 40 42 ]. In addition to the p16 + /HPV + cases we could identify in total 62 patients with p16 overexpression but HPV-DNA negative OPSCC (which is a rate of 4.9% of false positive p16 cases).This rate is comparable with the predicted rate of false positive p16 cases (3.8%) calculated by a recently published formula of Gallus et al [ 42 ]. Recent studies [ 9 , 37 , 40 42 ] found that patients with p16 + /HPV- OPSCC seem to have the same prognosis or only slightly better than p16-/HPV- cases.…”
Section: Discussionmentioning
confidence: 99%
“…This has a potential detrimental effect on patient stratification and selection for deintensification protocols in these populations, and it could, theoretically, also affect HPV detection in subsites other than the oropharynx, where the HPV reported prevalence is often low. In fact, an ever-growing amount of evidence discourages its use as a surrogate marker of HPV infection outside of the oropharyngeal site and, in particular, in LSCCs, as well as under specific conditions (a low prevalence of HPV-related oropharyngeal squamous cell carcinoma), even for the oropharyngeal site [ 5 , 14 , 59 , 60 , 61 , 62 ]. The last decade of research on the topic seems to also minimize its potential biologic role in the cancerogenic process of LSCCs, probably impacting only a small subgroup of patients.…”
Section: P16 Ink4amentioning
confidence: 99%
“…Therefore, the correct definition of HPV-driven carcinogenesis as part of the work-up is of paramount importance, and the possibility of false-positive findings at sole p16immunohistochemistry should not be underestimated [80,81]. In populations with a rate of HPV-driven SCC in the oropharynx below 40%, p16 overexpression should be integrated with nucleic acid detection to confirm HPV-driven carcinogenesis and draw proper clinical considerations [82,83].…”
mentioning
confidence: 99%